1992
DOI: 10.1073/pnas.89.17.8249
|View full text |Cite
|
Sign up to set email alerts
|

Yeast artificial chromosomes for the molecular analysis of the familial polyposis APC gene region.

Abstract: Two yeast artificial chromosomes (YACs) spanning a total distance of 1.1 megabase pairs of DNA around the MCC (for mutated in colorectal carcinoma) and APC (for adenomatous polyposis coli) genes at 5q21 have been isolated and characterized. Starting from the MCC gene, a strategy was undertaken to identify constitutional submicroscopic deletions in familial adenomatous polyposis patients that might considerably narrow down the position of the APC gene. To this end, YACs identified by the MCC gene were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(42 reference statements)
0
3
0
1
Order By: Relevance
“…Cytogenetically detectable interstitial deletions at the chromosomal region 5q22 have been reported in several patients exhibiting FAP and some degree of mental retardation and dysmorphism, [13][14][15][16][17][18] and were the key observation for mapping and cloning of APC. [19][20][21][22][23] Since then, a few submicroscopic deletions have been detected in FAP patients of normal intelligence and without dysmorphic features by different methods, including apparent non-parental segregation of intragenic or flanking polymorphic marker alleles, fluorescent in situ hybridisation (FISH) analysis with clones from chromosomal region 5q22, quantitative PCR, comparative genomic hybridisation, or RNA analysis. 14 24-28 All of these methods examine part of the coding sequence or flanking regions.…”
mentioning
confidence: 99%
“…Cytogenetically detectable interstitial deletions at the chromosomal region 5q22 have been reported in several patients exhibiting FAP and some degree of mental retardation and dysmorphism, [13][14][15][16][17][18] and were the key observation for mapping and cloning of APC. [19][20][21][22][23] Since then, a few submicroscopic deletions have been detected in FAP patients of normal intelligence and without dysmorphic features by different methods, including apparent non-parental segregation of intragenic or flanking polymorphic marker alleles, fluorescent in situ hybridisation (FISH) analysis with clones from chromosomal region 5q22, quantitative PCR, comparative genomic hybridisation, or RNA analysis. 14 24-28 All of these methods examine part of the coding sequence or flanking regions.…”
mentioning
confidence: 99%
“…目前也有许多靶向敲除的小鼠如 Msh2 敲除小 鼠 [7] 、k-ras 敲除小鼠 [8] 、p53 敲除小鼠等 [9] 。研究者 将几种突变或敲除小鼠的后代杂交繁殖, 形成新品 系的突变-敲除小鼠, 用来研究几种不同蛋白同时发 生失活和/或激活的效应。迄今, 和肠道肿瘤相关的 基因突变小鼠或敲除小鼠大约有 30 多种 [10] 育过程中关键的信号转导途径 [11] , 也对肿瘤的发生 发展起到不同寻常的作用 [12] 。诸多研究支持结直肠 [16] 。大量研究表明多于 75% 的已知突变落于第 15 外显子的突变成簇区(mutation…”
Section: Apc(min/+)突变小鼠。unclassified
“…Mutations within the adenomatous polyposis coli (APC) gene have been demonstrated to represent the molecular basis of FAP Nishisho et al 1991). The APC gene has been cloned in yeast artificial chromosomes (Hampton et al 1992) and the cDNA sequence of the APC transcript has been reported . The initial analysis of APC-specific transcripts revealed that heterogeneity of mRNAs existed because of alternative splicing events, affecting APC exon 9.…”
Section: Introductionmentioning
confidence: 99%